Analisis Peran Auditor Internal dalam Pencegahan Potensi Fraud pada PT. Menara Dunia Tour Travel - Meiyola Krisma Agatha; Rizki Luthfi Aulia; Irda Agustin Kustiwi (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to analyze fraud and acts of fraud that occurred at PT. Menara Dunia Tour Travel, is able to increase knowledge and study the role of internal auditors in preventing potential fraud at PT. World Tower Tour Travel. This research uses a qualitative method with a case study approach. The data collection technique used in this research is interviews. The type of data used is primary data. The results of this research show that (1) There is the potential for fraud to occur due to abuse of position authority, misuse of funds to increase the budget to enrich oneself which has the potential to cause losses to the company, (2) Internal auditors in preventing fraud have an independent, honest and also have responsibility for completing their work so that the level of fraud that occurs in the company can be prevented and reduced.